Sex Differences in Parkinson’s Disease: A Narrative Review - Carlo Cattaneo; Javier Pagonabarraga (Neurology and Therapy)
Abstract Sex differences in epidemiology, clinical features, and therapeutical responses are emerging in several movement disorders, even though they are still not widely recognized. Parkinson’s disease (PD) is not an exception: men and women suffering from PD have different levels of disability. Research has been performed using multiple databases and scientific journals; this review summarizes the available evidence on sex differences in PD regarding epidemiology, risk factors, genetics, clinical phenotype, social impact, and therapeutic management. The role of hormones in determining such differences is also briefly discussed. The results confirm the existence of differences between men and women in PD; women have a higher risk of developing disabling motor complications and non-motor fluctuations compared to men, while men have a higher risk of developing cognitive impairment, postural instability, and gait disorders. Improving our knowledge in these differences may result in the implementation of strategies for disease-tailored treatment and management.